The curative treatment and approach to preventive care of bovine respiratory disease complex (BRDC) - Zaid ZOUAGUI; Hicham AIT LBACHA (Revue Marocaine des Sciences Agronomiques et Vétérinaires, 2019)
The bovine respiratory disease complex (BRDC) remains one of the major diseases affecting modern cattle breeding. This debilitating and sometimes lethal complex has a considerable economic impact in terms of production losses and reduced productivity. The multitude of aetiologies causing and risk factors associated with this pathology render its control difficult. This literature review presents current therapeutic and preventive approaches against BRDC.